Informational legal relations in labor law of Ukraine through the prism of labor law information - Vakaryuk, Lyudmyla (Baltija Publishing, 2021)
The legal nature of information legal relations in labor law is studied in the article through the prism of labor law information. It is emphasized that the information recognized as labor law information is necessary for the implementation of employees and employers of individual and collective labor rights within the employment relationship. It is noted that labor law is a branch of law where information is one of the factors in the effective implementation of the subjects of labor law of their rights and responsibilities. In addition, in labor law there is a whole system of information relations as part of not only labor but also derived legal relations. The information labor space has been formed in the domestic labor legislation, with a certain set of information relations as public, regulated by the norms of labor law, the subjects of which are the bearers of mutual information rights and responsibilities. It is possible to define information relations in labor law by means of the concept of information relations which has developed in science of information law, and distinctive specific signs of the information in labor law. It is given the definition of the concept of information relations in labor law as a special type of relationship between the subjects of labor law for the search, collection, storage, processing, accumulation, transmission, provision, dissemination and processing of labor law information.